1986
DOI: 10.1136/gut.27.10.1120
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal and gastric motility disorders in patients categorised as having primary anorexia nervosa.

Abstract: SUMMARY Gastrointestinal motor function in patients with primary anorexia nervosa has rarely been investigated. We studied oesophageal motor activity in 30 consecutive patients meeting standard diagnostic criteria for primary anorexia nervosa (Feighner et al; DSM III). Seven were found to suffer from achalasia instead of primary anorexia nervosa, one from diffuse oesophageal spasm and one from severe gastro-oesophageal reflux and upper oesophageal sphincter hypertonicity, while partly non-propulsive and repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
79
1
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 15 publications
3
79
1
2
Order By: Relevance
“…Interestingly, studies using an OGTT have also found a delay in the insulin response curve in both ill (39) and weight-restored AN subjects (10). Gastric and gut dysmotility associated with AN (26,34) may be an additional factor contributing to the right shift in glucose and insulin response curves observed in AN compared with control subjects, and the lower AUC for glucose and insulin in starved AN may reflect malabsorption. We cannot, however, explain why the AUC for insulin at AN1 is comparable to that of controls whereas it is depressed at AN2 and AN3 as though there is increased sensitivity to insulin with refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies using an OGTT have also found a delay in the insulin response curve in both ill (39) and weight-restored AN subjects (10). Gastric and gut dysmotility associated with AN (26,34) may be an additional factor contributing to the right shift in glucose and insulin response curves observed in AN compared with control subjects, and the lower AUC for glucose and insulin in starved AN may reflect malabsorption. We cannot, however, explain why the AUC for insulin at AN1 is comparable to that of controls whereas it is depressed at AN2 and AN3 as though there is increased sensitivity to insulin with refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, achalasia, which often presents with dysphagia, regurgitation of food, weight loss, and avoidance of eating, has been described in case reports [2][3][4][5][6] and series 7 to have been misdiagnosed as anorexia nervosa. Desseilles et al 2 describe the case of a 24-year-old man presenting with weight loss and postprandial vomiting, and diagnosed with an atypical eating disorder, who was subsequently discovered to have a grossly dilated esophagus due to achalasia.…”
Section: Discussionmentioning
confidence: 96%
“…Marshall and Russell 5 describe a 30-year-old woman who was treated on a psychiatric unit for atypical anorexia nervosa for 2 months, before the correct diagnosis of achalasia was made. Finally, Stacher et al 7 reported on a series of 30 patients meeting the criteria for anorexia nervosa, seven of whom were found to have primary achalasia causing their symptoms. In a related article, 6 they note that while inadequate history-taking and clinical bias can contribute to misdiagnosis, patients themselves may come to misinterpret their physical symptoms as being psychological in origin.…”
Section: Discussionmentioning
confidence: 97%
“…Although reports of achalasia in adults and adolescents misdiagnosed as eating disorders exist in the literature (Kenney, 1984;Stacher, Kiss, Wiesnagrotzki, Bergmann, Hö bart, & Schneider, 1986;Stacher, Wiesnagrotzki, & Kiss, 1990;Wright, Smith, & Mitchell, 1990), the differential diagnosis of anorexia nervosa can cause diagnostic confusion. In the case just presented, the patient had lost weight and had a number of additional problems; yet two core criteria for a diagnosis of anorexia nervosa have not been met: the patient presented no body image distortion, and the absence of somatic pathology was not confirmed.…”
Section: Discussionmentioning
confidence: 97%